TINJAUAN HUKUM PERATURAN PEMERINTAH NOMOR 5 TAHUN 2021 TENTANG PENYELENGGARAAN PERIZINAN BERBASIS RISIKO TERHADAP INVESTASI BERBASIS OSS (ONLINE SINGLE SUBMISSION) - Asna, Royatul; Sadiyah, Karisma Aliatus (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This paper discusses Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Licensing, which aims to create a better investment climate in Indonesia. By categorizing business activities into low, medium, and high risk categories, the government seeks to accelerate the licensing process and encourage economic growth without neglecting environmental protection. This study uses a legislative and sociological approach to analyze the social impact of implementing risk-based licensing on society. Through a literature study, data were collected from related laws and regulations and literature, which were then analyzed qualitatively. The results of the study show that the risk-based licensing system, supported by the Online Single Submission (OSS) platform, not only simplifies the licensing process for business actors, but also increases transparency and public trust, and reduces corrupt practices. This study is expected to provide a comprehensive picture of the implementation of risk-based licensing and its contribution to investment in Indonesia.